Evaluating Antimicrobial Effects of Centaurea Plant's Essential Oil on Pathogenic Bacteria: Staphylococcus Aureus, Staphylococcus Epidermidis, and Escherichia Coli Isolated from Clinical Specimens - Haedeh Mobaiyen; Abolfazl Jafari Sales; Javad Sayyahi (Fasa University of Medical Sciences, 2015)
Background & Objectives :Nowadays, development of drug resistance against chemical antimicrobial drugs has attracted attention using medicinal plants in treatment of infections. The aim of this study is to evaluate the antimicrobial effects of two species of Centaurea plant's essential oil on drug resistant clinical isolates of three pathogenic isolates. Materials & Methods :The studied plants were collected from Marand city in East Azerbaijan, Iran and were confirmed as Centaurea Depressa M.B. and Centaurea Cyanus L. by botanists of Iran Agriculture Organization. The essential oil of these plants (Stems and leaf) were extracted via steam distillation method by Clevenger, and their antimicrobial effects were studied by well diffusion method in the abovementioned bacteria. The components of essential oil were identified by injection to gas chromatography linked to mass spectrometry (GC/M). Results :The results of this study prove that the essential oils from the abovementioned plants have bactericidal effects. The most antibacterial effect is observed in Escherichia coli strains. The results of GC/MS chromatography reveal that the essential oils of Centaurea Depressa M.B. and Centaurea Cyanus L. have 28 and 32 compounds, respectively. Conclusion: This study confirmed that the grasses could be used in medicinal plants group with antibacterial properties. However, their effects in vivo must be evaluated and the most effective component of them must be identified carefully so that they can be applied commonly as an alternative synthetic drug in treating infections.